Geo-History Notes for the Study of Production of the Beach Space in Northeastern, Brazil - Alves dos Santos, Otávio Augusto (Sociedade & Natureza, 2023)
The present work aims to present some geohistorical notes about the production of beach space in Northeast Brazil, based on bibliographic research. The Brazilian beach space results from different social practices, some of which emerged through the absorption of behaviors and lifestyles arising from modern westerns. The social appropriation of beaches on the coast of the Northeast took place in the mid-19th century, when local elites turned to the sea, in the context of the incorporation of the so-called "modern maritime practices" (therapeutic baths, vacations, etc.), colonizing an environment previously intended only for “traditional maritime practices” (fishing, defense, and port activity). The transformation and consumption of these spaces were based on the establishment of second homes and infrastructure aimed at the development of tourist activity. In the first part of this article, we characterize the environment and socially on the Northeastern coast, in order to demonstrate the predominance of the beach environment and its social and economic value. Then we seek to discuss the production of beach space in the Northeast, pointing out the geohistorical factors linked to its valorization. Finally, we briefly present the process of production of beach space in a large northeastern city, Recife, highlighting the historical process of appropriation and valorization of its beaches.